14. PERCENTAGE OF PERITONEAL DIALYSIS PATIENTS WHO PRACTICE CORRECT FLUID REPLACEMENT PROCEDURES AND RELATED FACTORS AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the rate of correct practice of self-fluid exchange procedures in peritoneal dialysis patients at home and factors related to hand washing compliance in self-fluid exchange procedures in peritoneal dialysis patients.Subjects and methods: Cross-sectional description, performed in 60 patients being treated with continuous peritoneal dialysis at the Department of Nephrology - Dialysis, Thong Nhat Hospital from March to September 2023 to Evaluate compliance with the fluid exchange process (25 steps).Results: The median age of study subjects was 55 years, quartiles (42-67). Peritoneal dialysis training time had a median of 7 quartiles (4-11). The number of compliance steps is 22 (±2), compliance is at least 16 steps, 5% comply with all 25 steps. Compliance with 16 to 25 steps reaches a rate of 90% or more. The rate of correct hand washing in 6 steps is (59.3%-80.3%), the rate of correct routine hand washing is higher in the group under 60 years old, office workers have a higher rate of correct hand cursing with p < 0.05.Conclusions: The average number of compliance steps is 22 (± 2) and 5% of participants to complete all 25 steps. The low compliance step involves checking the fluid bag, preparing the fluid bag, performing routine hand hygiene, and checking the expiration date. There is a relationship between hand hygiene compliance and age and occupation in home peritoneal dialysis patients.
Keywords: Practice correct procedures; hand hygiene; peritoneal dialysis